ANALISIS YURIDIS PELANGGARAN NOTARIS TERKAIT DENGAN TEMPAT KEDUDUKAN DAN WILAYAH JABATAN NOTARIS DI KABUPATEN SIMALUNGUN - DEFINA ANGGRIANI SIMANGUNSONG (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Suprayitno2. Rudy Haposan3. Tony In doing his job to draw up authentic deeds, a Notary has to be limited in his working area which is in his own province. In practice, however, some Notaries have violated against the regulation concerning their working area, and some of them even have more than one office. The sanction will, of course, be imposed on them. Their non-compliance with the regulation concerning their position and their working area is related to the violation against the Notarial Act, Oath of Notarial Position, and Notarial Code of Ethics. The sanction can be dismissal, suspension, and dishonorable dismissal. Some factors which make a Notary do his job outside of his working area are related to drawing up deeds, regional extension, lack of Notaries in the remote areas, the Notarial Act, Oath of notarial position, Notarial Code of Ethics, and notarial supervision and couching.Keywords: Violation, Notary, Notary’s Position and Working Area